Endodontic treatment of the young permanent teeth - Aleksandrov Smiljana (Stomatološki glasnik Srbije, 2004)
Pulp treatment in the young permanent teeth represents significant problem in peadiatric dentistry. The aim of this paper was to present the course of endodontic treatment of a young permanent tooth and success after 26 years. Upper right central incisor remained functional following thorough endodontic therapy, temporary root canal filling with calciumhydroxide and final root obturation. After 26 years from the beginning and completion of endodontic treatment, the tooth is still in normal funciton.